Egypt and the Gulf a renewed regional policy alliance - Mason, Robert (Gulf Research Centre book series, 2017)
The book's main argument derives from a complex web of political, socio-economic and military issues in a changing regional and international system. It states that the Egyptian regional policy under Sisi will generally remain consistent with existing parameters (such as broad counter-terrorism efforts, including against the Muslim brotherhood). There is strong evidence to support the idea that Cairo wishes to maintain a GCC-first policy.